Solid waste management in a higher education institution in the western Amazon, Brazil - Castro, Lenimar de Rebouças de; Marques, Evely Laranjeira; Marques, Francinete Soares; Alves, Rodrigo Couto (Brazilian Journal of Production Engineering, 2024)
Waste generation in universities has become a challenge over the years, mainly due to the lack of correct management. The present study aims to analyze the management of solid waste at a higher education institute (HEI) located in Amazonas. In the first stage, solid waste gravimetry was carried out at three different moments. Next, each stage of waste management was analyzed, including segregation, packaging, internal transport, temporary storage, collection and external transport and final disposal. It was found that the IES generates 44.56% of organic waste, 36.18% of recyclable materials, and 19.23% of waste equivalent to waste generated. In the analysis of the waste management system, it was found that the IES needs adjustments such as the destination of waste and the care taken with the collection of hazardous waste. With a positive evaluation, the collection of recyclables is carried out by the municipality’s collectors’ association and the correct disposal of hazardous waste, which takes place by a licensed company. Therefore, it is understood that IES has a functioning waste management system, but that it still needs improvements.